Dana Desa dan Perkembangan Status Desa: Studi Kasus Kabupaten/Kota di Indonesia - Aji, Yore Isti Tosan; Qibthiyyah, Riatu Mariatul (UI Scholars Hub, 2023)
Village development and improving village status are among the main agendas of the Indonesian Government. Village fund maybe have an important role, however, empirical studies on village funds and village status are still limited. This study aims to prove impact of the village fund on the development of village status according to the Village Development Index in Indonesia. Using First Difference method between 2014 and 2018, we found that village funds had a partially significant impact on the development of village status. Although statistically significant, the regression coefficient shows a small economic impact.